Developing evaluation capacities in integrated care projects: Lessons from a scientific support mission implemented in Belgium - Charlier, Nathan; Colman, Elien; Alvarez Irusta, Lucia; Anthierens, Sibyl; Van Durme, Thérèse; Macq, Jean; Pétré, Benoit (Frontiers in Public Health, 2022)
The capacity of self-assessment, to learn from experience, to make information-based decisions and to adapt over time are essential drivers of success for any projects aiming at healthcare system change. Yet, many of those projects are managed by healthcare providers’ teams with little evaluation capacity. In this article, we describe the support mission delivered by an interdisciplinary scientific team to 12 integrated care pilot projects in Belgium, mobilizing a set of tools and methods: a dashboard gathering population health indicators, a significant event reporting method, an annual report, and the development of a sustainable “learning community”. The article provides a reflexive return on the design and implementation of such interventions aimed at building organizational evaluation capacity. Some lessons were drawn from our experience, in comparison with the broader evaluation literature: the provided support should be adapted to the various needs and contexts of the beneficiary organizations, it has to foster experience-based learning, and requires all stakeholders to adopt a learning posture. A long-time, secure perspective should be provided for organizations, and the availability of data and other resources is an essential precondition for a successful work.